2015
DOI: 10.1002/ppap.201500176
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Charging on Unconventional Surface Morphologies of PMMA Substrates During Ar Plasma Etching

Abstract: The charging on unconventional, rough, surface morphologies of polymeric substrates is investigated. The case study is Ar plasma etching of PMMA surfaces with sinusoidal profiles resembling rough profiles. A modeling framework for the description of charging on plasma ''wetted'' two-dimensional (2d) surface morphologies is developed. It consists of models for the calculation of the ion and electron trajectories, the local surface charge density, the potential induced by the surface charge, and a surface etchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 52 publications
2
37
0
Order By: Relevance
“…Another possible factor is the surface charge accumulated on the dielectric surface, which is largely dependent on the types of dielectric material . Li et al reported that the desorption of the trapped electrons on the dielectric surface can provide seed electrons for the diffuse discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible factor is the surface charge accumulated on the dielectric surface, which is largely dependent on the types of dielectric material . Li et al reported that the desorption of the trapped electrons on the dielectric surface can provide seed electrons for the diffuse discharge.…”
Section: Discussionmentioning
confidence: 99%
“…θ in Equation is the angle of ion incidence (with respect to the normal to the surface). The angle dependence being expressed by f ( θ ), is approximated by a simple polynomial function aiming to approximate the measured or simulated curves of angle dependent etching yield of polymeric substrates: f(θ)=true{centera,θφ1centerb0+b1θ+b2θ2+b3θ3,φ1θφ2center1+c(θφ2)2,θφ2true}. …”
Section: Case Study: Etching Of a Polymeric Substrate By Ar Plasma Inmentioning
confidence: 99%
“…The space [0, φ 1 ] defines the angle range that the etching yield is constant and equal to that at normal incidence. The reported values for φ 2 for Ar + sputtering of several polymeric substrates varies from 60° to 80° . a in the same works varies from 0.67 to 0.13 or even lower depending on the ion energy.…”
Section: Case Study: Etching Of a Polymeric Substrate By Ar Plasma Inmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent work of Memos and Kokkoris has recognized that the rough surface of dielectric materials being etched by plasma indeed presents the charging effect. This is because the roughness results in a local imbalance of negative and positive charges accumulated on dielectric surface.…”
Section: Introductionmentioning
confidence: 99%